Русский капитал. От Демидовых до Нобелей - Чумаков Валерий (Другая история, 2008)
Экземпляры: (03.12.2009) / Инвентарный номер: 45711 / Цена: 250.00 / Сис.шифр: 65.9(2)09 45711 / Авт.знак: Ч-90 / ББК: 65.9(2)09